Arrhythmogenic left ventricular cardiomyopathy caused by a novel likely pathogenic DSP mutation, p.K1165Rfs*8, in a family with sudden cardiac death - Amir Azimi; Maryam Pourirahim; Golnaz Houshmand; Sara Adimi; Majid Maleki; Samira Kalayinia (BMC Medical Genomics, 2023)
Abstract Objective We conducted an investigation into the clinical and molecular characteristics of Arrhythmogenic left ventricular cardiomyopathy (ALVC) caused by a novel likely pathogenic mutation in an Iranian pedigree with sudden cardiac death (SCD). Background ALVC is a genetically inherited myocardial disease characterized by the substitution of fibro-fatty tissue in the left ventricular myocardium, predominantly inherited in an autosomal dominant pattern and is commonly associated with genes involved in encoding desmosomal proteins, specifically Desmoplakin (DSP). Methods The patient and available family members underwent a comprehensive clinical assessment, including Cardiac magnetic resonance (CMR) imaging, along with Whole-exome sequencing (WES). The identified variant was confirmed and segregated by Polymerase chain reaction (PCR) and Sanger sequencing in the family members. Results A novel likely pathogenic heterozygous variant, DSP (NM_004415.4), c.3492_3498del, p.K1165Rfs*8 was discovered in the proband. This variant is likely to be the primary reason for ALVC in this specific family. This variant was confirmed by Sanger sequencing and segregated in other affected members of the family. Conclusion We identified a novel likely pathogenic variant in the DSP gene, which has been identified as the cause of ALVC in an Iranian family. Our investigation underscores the importance of genetic testing, specifically WES, for individuals suspected of ALVC and have a family history of SCD.